Novel inhibitors of Mycobacterium tuberculosis GuaB2 identified by a target based high-throughput phenotypic screen - Cox, Jonathan A G; Mugumbate, Grace; Peral, Laura Vela-Glez Del; Jankute, Monika; Abrahams, Katherine A; Jervis, Peter; Jackenkroll, Stefan; Perez, Arancha; Alemparte, Carlos; Esquivias, Jorge; Lelièvre, Joël; Ramon, Fernando; et al. (Nature Research, 2022)
High-throughput phenotypic screens have re-emerged as screening tools in antibiotic discovery. The advent of such technologies has rapidly accelerated the identification of 'hit' compounds. A pre-requisite to medicinal chemistry optimisation programmes required to improve the drug-like properties of a 'hit' molecule is identification of its mode of action. Herein, we have combined phenotypic screening with a biased target-specific screen. The inosine monophosphate dehydrogenase (IMPDH) protein GuaB2 has been identified as a drugable target in Mycobacterium tuberculosis, however previously identified compounds lack the desired characteristics necessary for further development into lead-like molecules. This study has identified 7 new chemical series from a high-throughput resistance-based phenotypic screen using Mycobacterium bovis BCG over-expressing GuaB2. Hit compounds were identified in a single shot high-throughput screen, validated by dose response and subjected to further biochemical analysis. The compounds were also assessed using molecular docking experiments, providing a platform for their further optimisation using medicinal chemistry. This work demonstrates the versatility and potential of GuaB2 as an anti-tubercular drug target.